2015
DOI: 10.1519/jsc.0000000000000792
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Development of Anthropometric and Physical Characteristics Within Academy Rugby League Players

Abstract: 1The purpose of the present study was to evaluate the annual and long-term (i.e., 4 2 year) development of anthropometric and physical characteristics in academy (16-20 years) 3 rugby league players. Players were assessed at the start of pre-season over a six year period 4 and were required to be assessed on consecutive years to be included in the study n=35; n=44; n=35; n=16). A subset of 15 6 players were assessed for long-term changes over 4 years . Anthropometric 7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 31 publications
1
69
1
3
Order By: Relevance
“…4,23 However, as height demonstrated the largest effects between the levels this may be a more important contributor towards career attainment in rugby league and may therefore be used as a potential identification measure within players aged 17-19 years, especially as this was the only measure assessed that was not trainable. However, current findings differ from previous research in younger (13)(14)(15)(16) years) rugby league players whereby no differences were identified for body size with future career attainment. 6 Maturational processes may impact upon the development of body size in younger players 24,25 suggesting that height may only be a useful identification tool post maturation in rugby league player identification.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…4,23 However, as height demonstrated the largest effects between the levels this may be a more important contributor towards career attainment in rugby league and may therefore be used as a potential identification measure within players aged 17-19 years, especially as this was the only measure assessed that was not trainable. However, current findings differ from previous research in younger (13)(14)(15)(16) years) rugby league players whereby no differences were identified for body size with future career attainment. 6 Maturational processes may impact upon the development of body size in younger players 24,25 suggesting that height may only be a useful identification tool post maturation in rugby league player identification.…”
Section: Introductioncontrasting
confidence: 99%
“… Physical qualities should be considered in the identification and development of elite [16][17][18][19] year old rugby league players due to their contribution to future career attainment.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Existing research has investigated the physical characteristics of adolescent rugby players by age (21,38), position (12,41) and level (21,36). Till et al (38) observed that adolescent rugby players have significant annual improvements in their anthropometric and physical characteristics, which were greatest between 16 and 17 years compared to their older counterparts (18 to 20 year old) and likely demonstrate that greater changes occur in younger individuals upon the commencement of a structured training programme.…”
Section: Introductionmentioning
confidence: 99%
“…Till et al (38) observed that adolescent rugby players have significant annual improvements in their anthropometric and physical characteristics, which were greatest between 16 and 17 years compared to their older counterparts (18 to 20 year old) and likely demonstrate that greater changes occur in younger individuals upon the commencement of a structured training programme. This has been supported with recent work demonstrating that players who have a younger training age tend to develop at a greater rate than their more experienced counterparts (37).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of testing is used to profile individuals against norms for their position within the respective sports (12,30). The data are used to provide valuable insights into factors that may contribute to and regulate exercise performance, and should be considered complimentary in guiding the preparation of individuals to improve their physical potential; thus allowing them to tolerate the demands of training and match-play to excel in their chosen sport (27).…”
Section: Introductionmentioning
confidence: 99%